Spanish automatic text enrichment - Felice, Mariano (2009)
Unlike text on paper, hypertext enables the linking of pieces of text with other texts and multimedia resources, which not only improves the waywe read but also lays the foundation for new information systems. Specifically, the proliferation of collaborative sites, blogs, online databases, encyclopedias and many other services on the World Wide Web provides an invaluable source of up-to-date information which can be used to aid reading comprehension. As a result, an approach to the automatic extraction, merging and integration of online information is proposed for the purpose of “enriching” texts. This unprecedented text enrichment process allows users to transform ordinary plain texts into self-explanatory hypertexts containing contextual information and resources selected automatically from the Web. Application of such an enrichment process could help students in their scholarly reading, provide users with related multimedia resources and avoid multiple searches for concepts and entities mentioned in a text, among other purposes